2016
DOI: 10.2319/021016-115.1
|View full text |Cite
|
Sign up to set email alerts
|

Microleakage under ceramic flash-free orthodontic brackets after thermal cycling

Abstract: Objective: To compare microleakage under 3M Unitek's APC Flash-Free Adhesive Coated System bracket and the APC PLUS Adhesive Coated System bracket after thermal cycling. Materials and Methods: Forty freshly extracted human maxillary premolars were randomly divided into two groups and bonded with either a Flash-Free bracket or a PLUS bracket. After bonding, the samples were incubated in a water bath at 378C for 24 hours and thermocycled for 5000 cycles between 58C and 508C. All teeth were immersed in a 2% methy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…A limited amount of studies were found that evaluated APC FF (2,5-11). Three of these confirmed some of the benefits anticipated by the manufacturer, such as time savings during bracket bonding (7,8,11), even up to one third compared with a conventional orthodontic adhesive as has been recently stated by Grünheid et al (11); or no need for flash removal after placement (7,9-11). Three of the manuscripts (6,8,9) evaluated the SBS obtaining high bond strength values.…”
Section: Introductionsupporting
confidence: 75%
“…A limited amount of studies were found that evaluated APC FF (2,5-11). Three of these confirmed some of the benefits anticipated by the manufacturer, such as time savings during bracket bonding (7,8,11), even up to one third compared with a conventional orthodontic adhesive as has been recently stated by Grünheid et al (11); or no need for flash removal after placement (7,9-11). Three of the manuscripts (6,8,9) evaluated the SBS obtaining high bond strength values.…”
Section: Introductionsupporting
confidence: 75%
“…Mean microleakage scores in all the 3 systems of stainlesssteel brackets were higher at both occlusal and gingival side of the bracket than the scores with conventional, APCP, and APCF ceramic bracket systems reported in the previous studies. 7,25 A possible explanation for this finding is the "incomplete polymerization" phenomenon. In restorative dentistry, researchers have documented several factors that affect the depth of photoactivated cures, including duration and intensity of light exposure, filler type and shade of adhesive resin, and the reflective characteristics of the adhesive resin bulk.…”
Section: Discussionmentioning
confidence: 99%
“…Arhun et al 9 showed increased microleakage with metal brackets compared to ceramic brackets and on the brackets gingival side compared to the occlusal side. Kim et al 7 compared microleakage under APCP and APCF ceramic brackets and reported no significant difference between the systems in the extent of microleakage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although in-vitro investigations do not perfectly resemble clinical situations, they are helpful in standardizing study conditions and controlling for confounding factors related to individual patient biology and/or behavior. Similar experimental methodology has been followed in previous studies assessing bonding strength and microleakage of novel flash-free bracket systems [ 22 , 23 ], providing reliable clinical information. Research evaluating the clinical properties of orthodontic wires is also conducted in a controlled in vitro design, leading to conclusions that help clinicians select appropriate wires in their clinical practice based on their performance rather than their advertised features that are often misleading [ 24 , 25 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%